Literasi Digital untuk UMKM Gumasep: Program Magang Mahasiswa UPI Kampus Sumedang - Gusrayani, Diah; Rukmana, Kusman (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Small and Medium Enterprises (SMEs) or UMKM in Sumedang Regency have been a priority for a long time but were restructured under the Department of Industry and Trade’s SME division in 2015 (RPJMD, 2015). On the other hand, students from UPI Sumedang Campus act as agents of change for the community. At Sumedang Campus, dozens of students enroll in entrepreneurship courses equipped with a strong theoretical foundation, including entrepreneurship education, social entrepreneurship, and business creativity. One of the indicators of UPI’s 2021-2025 Strategic Plan (RENSTRA), which is highly relevant to this student internship program, is the increase in educational and non-educational innovations resulting from flagship research on national, regional, and international scales. The innovation that will be developed in this community service is a simple application like a smart cashier, which will facilitate buying and selling transactions at the outlet where the internship is conducted. The internship activities begin with data collection to identify problems, followed by focused group discussions (FGD), dialogues with related parties, and concluding with a problem-solving workshop. The activities were evaluated by interviewing all SME participants involved at the Gumasep Outlet, with 94% reporting they were greatly helped by this program.